(untitled) (Research, Society and Development, 2023)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurological disorder that is associated with poor brain performance. Individuals with ADHD have dyslexia, a certain impulsiveness and difficulty concentrating, resulting in poor school development. Taking into account, about 2.5 million new cases are declared per year in Brazil, whether due to real necessity or mere mediocrity of the diagnosis. Lisdexamfetamine methylphenidate is the main representative of a new class of long-acting agents for the treatment of ADHD, in current scenarios it has been the drug traditionally used as first choice for the treatment of children and adolescents with ADHD. Therefore, the general objective of this study was to analyze the effects that lisdexamfetamine dimesylate has for individuals with ADHD. In the methodology, a literature review was carried out, including studies in Portuguese and published between 2017 and 2022. Data collection took place in PubMed, LILACS, Scielo and Google Scholar databases. In the results, the safety and efficacy of lisdexamfetamine dimesylate for patients with ADHD proved to be effective and positive. In the studies found, it was understood that this drug has as its mechanism of action the blockade of the reuptake of the neurotransmitter dopamine and the stimulus to its production and noradrenaline. This action is what makes the stimulant of this medicine effective.